“[…] WE COULD JUST EAT SOMETHING”. LEOPOLD BUCZKOWSKI ON RESOLVING WARTIME CHAOS IN THE WORLD - Wróbel , Łukasz (Prace Polonistyczne, 2024)
This article has two aims: to reconstruct the ideas about animal-human relations that permeate Leopold Buczkowski’s works, and to bring out the mythological and speculative aspects of his reflection on war that are indebted to Pre-Socratic philosophy, especially Heraclitus and Empedocles. Buczkowski pointed out that humankind had developed a number of methods of killing animals and humans, but he also emphasized that there was a way to temporarily offset the effects of war on the local level. This is made possible at a feast, understood as a limited space for peaceful coexistence where both humans and animals satisfy their hunger and communicate with each another.